Association between the risk of seizure and COVID‐19 vaccinations: A self‐controlled case‐series study. Issue 12 (29th October 2022) - Wan, Eric Yuk Fai; Ng, Vanessa Wai Sei; Chang, Richard Shek‐Kwan; Yan, Vincent Ka Chun; Chui, Celine Sze Ling; Wong, Carlos King Ho; Li, Xue; Lai, Francisco Tsz Tsun; Chan, Esther Wai Yin; Hung, Ivan Fan Ngai; Lau, Kui Kai; Wong, Ian Chi Kei
Abstract: Objective: The risk of seizure following BNT162b2 and CoronaVac vaccinations has been sparsely investigated. This study aimed to evaluate this association. Method: Patients who had their first seizure‐related hospitalization between February 23, 2021 and January 31, 2022, were identified in Hong Kong. All seizure episodes happening on the day of vaccination (day 0) were excluded, since clinicians validated that most of the cases on day 0 were syncopal episodes. Within‐individual comparison using a modified self‐controlled case series analysis was applied to estimate the incidence rate ratio (IRR) with 95% confidence intervals (CIs) of seizure using conditional Poisson regression. Results: We identified 1656 individuals who had their first seizure‐related hospitalization (BNT162b2: 426; CoronaVac: 263; unvaccinated: 967) within the observation period. The incidence of seizure was 1.04 (95% CI .80–1.33) and 1.11 (95% CI .80–1.50) per 100 000 doses of BNT162b2 and CoronaVac administered, respectively. Sixteen and 17 individuals, respectively, received a second dose after having a first seizure within 28 days after the first dose of BNT162b2 and CoronaVac vaccinations. None had recurrent seizures after the second dose. There was no increased risk during day 1–6 after the first (BNT162b2: IRR = 1.39, 95% CI = .75–2.58; CoronaVac: IRR = 1.19, 95% CI = .50–2.83) and second doses (BNT162b2: IRR = 1.36, 95% CI = .72–2.57; CoronaVac: IRR = .71, 95% CI = .22–2.30) of vaccinations. During 7–13, 14–20, and 21–27 days post‐vaccination, no association was observed for either vaccine. Significance: The findings demonstrated no increased risk of seizure following BNT162b2 and CoronaVac vaccinations. Future studies will be warranted to evaluate the risk of seizure following COVID‐19 vaccinations in different populations, with subsequent doses to ensure the generalizability .